DEVELOPMENT OF POP-UP BOOK MEDIA BASED ON ANIMATED VIDEO ON JAPANESE OCCUPATION MATERIAL FOR STUDENTS OF GRADE XI SMAN 2 SIAK HULU: Pengembangan Media Pop-Up Book Berbasis Video Animasi Materi Pendudukan Jepang Pada Siswa Kelas XI SMAN 2 Siak Hulu - Muhammad Riski Riski; Suroyo; Asyrul Fikri (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research aims to develop an innovative learning media in the form of a Pop-up Book integrated with animated video for teaching the topic of the Japanese occupation in Indonesia to 11th-grade students at SMAN 2 Siak Hulu. The study addresses the limited use of technology-based media in history learning, which is still dominated by conventional lectures and lacks visual learning aids. The development process adopted the ADDIE model, encompassing Analysis, Design, Development, Implementation, and Evaluation. The media was developed using Microsoft PowerPoint and enhanced with 2D and 3D visual elements, then converted into animated video format accessible via smartphones and projectors. Validation was conducted by subject matter experts and media experts, yielding